Semiotic Analysis of Phishing Mode Prevention Efforts Implemented through BCA Advertisements “Don’t Know? Kasih No!” - Ichsan, Lulu Afifah (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The rise of phishing crimes targeting all levels of society necessitates effective public education. BCA’s advertisement